The Role of Mature Market Mutual Funds in Emerging Markets : Myth or Mayhem? - Sy, Amadou (IMF Working Papers; Working Paper ;, 2004)
The expansion of the global mutual funds industry has been characterized by growth in mature as well as emerging markets. This has clearly contributed to the development of local securities markets in emerging market economies, which in turn, has been key in attracting investment inflows from overseas funds. A major concern, however, is that large foreign investors could significantly disrupt the stability of local capital markets in the event of a market shock, with systemic implications for the real economy. Our estimates suggest that while local investors remain the more important group in terms of market share, the influence of foreign funds cannot be discounted. Asset allocation decisions by mature market funds- both dedicated and crossover-in aggregate, could affect emerging markets. In particular, European mutual funds appear to play a much bigger role in emerging markets than their U.S. counterparts.